The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.smim.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Immune and regulatory functions of neutrophils in inflammatory bone loss

Abstract: Although historically viewed as merely anti-microbial effectors in acute infection or injury, neutrophils are now appreciated to be functionally versatile with critical roles also in chronic inflammation. Periodontitis, a chronic inflammatory disease that destroys the tooth-supporting gums and bone, is particularly affected by alterations in neutrophil numbers or function, as revealed by observations in monogenic disorders and relevant mouse models. Besides being a significant debilitating disease and health b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 219 publications
(291 reference statements)
3
99
0
3
Order By: Relevance
“…2 Whether the immunopathologic consequences of tissue neutropenia in LAD1 are replicated in other forms of neutropenia remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Whether the immunopathologic consequences of tissue neutropenia in LAD1 are replicated in other forms of neutropenia remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…1 The mucocutaneous lesions in LAD1 were widely assumed to be due to infections that were a result of the relative tissue neutropenia caused by the inability of LAD1 neutrophils to enter the tissue and control microbes. 2 However, recent work has shown that LAD1-associated oral disease is actually a microbe-induced hyperinflammatory response. 3,4 …”
mentioning
confidence: 99%
“…Furthermore, congenital diseases, such as leukocyte adhesion deficiency, that impair neutrophil chemotaxis result in severe peri- odontitis at an early stage in life (46,47). In the mouse subcutaneous chamber model of infection, the newly appreciated periodontal pathogen F. alocis elicits a local inflammatory response with extensive neutrophil recruitment as well as spread to remote tissues, inducing lung edema with neutrophil recruitment and causing acute kidney injury (10).…”
Section: Discussionmentioning
confidence: 99%
“…CP does not result from individual pathogens but rather from polymicrobial synergy and dysbiosis (4) associated with a dysregulated immune response inducing inflammation-mediated tissue damage (5). Host genetic components have also been implicated in CP, with multiple genes contributing cumulatively to the host's overall disease risk (or protection) through effects on the host immune response and the microbiome (6). Since the Human Microbiome Project (HMP) (7), microbiota have been analyzed based on partial sequencing of the 16S rRNA gene, with different numbers of healthy and CP samples.…”
mentioning
confidence: 99%